The wage effects of schooling under socialism and in transition: Evidence from Romania, 1950 - 2000 - Daniela Andren; John S. Earle; Dana Sapatoru (W.E. Upjohn Institute for Employment Research, 2004)
We estimate the impact of schooling on monthly earnings from 1950 to 2000 in Romania. Nearly constant at about 3-4% during the socialist period, the coefficient on schooling in a conventional earnings regression rises steadily during the 1990s, reaching 8.5% by 2000. Our analysis finds little evidence for either the standard explanations of such an increase in the West (labor supply movements, product demand shifts, technical change) or the transition-specific accounts sometimes offered (wage liberalization, border opening, increased quality of education). But we find some support for institutional and organizational explanations, particularly the high productivity of education in restructuring and entrepreneurial activities in a disequilibrium environment.
Keywords: I20; J23; J24; J31; O15; P23; P31; 330; returns to schooling; human capital; education; wage differentials; transition; Romania; Bildungsertrag; Humankapital; Lohnstruktur; Planwirtschaft; Übergangswirtschaft; Rumänien